Rapid Eye Movement Sleep Deprivation Induces Neuronal Apoptosis by Noradrenaline Acting on Alpha1 Adrenoceptor and by Triggering Mitochondrial Intrinsic Pathway - Somarajan, Bindu I. (Front Neurol, 2016)
Many neurodegenerative disorders are associated with rapid eye movement sleep (REMS) loss; however, the mechanism was unknown. As REMS loss elevates noradrenaline (NA) level in the brain as well as induces neuronal apoptosis and degeneration, in this study, we have delineated the intracellular molecular pathway involved in REMS deprivation (REMSD)-associated NA-induced neuronal apoptosis. Rats were REMS deprived for 6 days by the classical flower pot method; suitable controls were conducted and the effects on apoptosis markers evaluated. Further, the role of NA was studied by one, intraperitoneal (i.p.) injection of NA-ergic alpha1 adrenoceptor antagonist prazosin (PRZ) and two, by downregulation of NA synthesis in locus coeruleus (LC) neurons by local microinjection of tyrosine hydroxylase siRNA (TH-siRNA). Immunoblot estimates showed that the expressions of proapoptotic proteins viz. Bcl2-associated death promoter protein, apoptotic protease activating factor-1 (Apaf-1), cytochrome c, caspase9, caspase3 were elevated in the REMS-deprived rat brains, while caspase8 level remained unaffected; PRZ treatment did not allow elevation of these proapoptotic factors. Further, REMSD increased cytochrome c expression, which was prevented if the NA synthesis from the LC neurons was blocked by microinjection of TH-siRNA in vivo into the LC during REMSD in freely moving normal rats. Mitochondrial damage was re-confirmed by transmission electron microscopy, which showed distinctly swollen mitochondria with disintegrated cristae, chromosomal condensation, and clumping along the nuclear membrane, and all these changes were prevented in PRZ-treated rats. Combining findings of this study along with earlier reports, we propose that upon REMSD NA level increases in the brain as the LC, NA-ergic REM-OFF neurons do not cease firing and TH is upregulated in those neurons. This elevated NA acting on alpha1 adrenoceptors damages mitochondria causing release of cytochrome c to activate intrinsic pathway for inducing neuronal apoptosis in REMS-deprived rat brain.